2021
DOI: 10.1007/s11625-021-01001-1
|View full text |Cite
|
Sign up to set email alerts
|

Using citizen science data to monitor the Sustainable Development Goals: a bottom-up analysis

Abstract: Official data are not sufficient for monitoring the United Nations Sustainable Development Goals (SDGs): they do not reach remote locations or marginalized populations and can be manipulated by governments. Citizen science data (CSD), defined as data that citizens voluntarily gather by employing a wide range of technologies and methodologies, could help to tackle these problems and ultimately improve SDG monitoring. However, the link between CSD and the SDGs is still understudied. This article aims to develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 50 publications
3
33
0
1
Order By: Relevance
“…In a case study evaluation of 30 CS projects, Ballerini and Bergh [11] find that the projects do have concrete local impacts in terms of sustainability, such as educating and engaging communities and influencing local policy-making. As such, they could provide much-needed local and contextual data for the SDGs.…”
Section: Findings On Cs and The Sdgsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a case study evaluation of 30 CS projects, Ballerini and Bergh [11] find that the projects do have concrete local impacts in terms of sustainability, such as educating and engaging communities and influencing local policy-making. As such, they could provide much-needed local and contextual data for the SDGs.…”
Section: Findings On Cs and The Sdgsmentioning
confidence: 99%
“…However, the sustainability is mostly discussed for CS in general, and thus looks predominantly at technical and scientific phenomena [9]. Studies that frame CS explicitly in the context of the SDGs have also been observed in recent years [10], [11], [2]. Yet, a specific focus on CSS and the SDGs is missing so far.…”
Section: Introductionmentioning
confidence: 99%
“…Ma to szczególne znaczenie w kontekście osiągania celów zrównoważonego rozwoju nakreślonych w obszarze edukacji (SDG, ang. sustainable development goals) -cel nr 4 [Ballerini 2021]. Powiązanie nauki obywatelskiej z SDG umożliwia: wspólne kierowanie projektami nauki obywatelskiej, motywowanie społeczności do udziału w inicjatywach, otrzymywanie wsparcia w realizacji projektów, a także zwiększenie zainteresowania finansowaniem inwestycji [Ballerini 2021].…”
Section: Wyniki I Dyskusjaunclassified
“…A study [21] issued by the EU commission highlighted that environmental Citizen Science projects already contribute to a diversity of SDGs, in particular to health and well-being (SDG 3), climate mitigation and adaptation (SDG 13), terrestrial nature conservation (SDG 15), and global partnership for sustainable development (SDG 17). Thus, Citizen Science Data are suggested as a useful resource for complementing SDG reporting [22].…”
Section: Introductionmentioning
confidence: 99%